Academic administration guidelines to develop students to have learning skills In the 21st Century Case Study : School of Administrative Organization Uttaradit Province Uttaradit Province - Thangkham, Pruedsapa; Thammasit , Phimphaka; Panyasai, Vajee (Journal of Modern Learning Development, 2022)
The purpose of this research was to study the current condition and the need for academic administration. and to study the guidelines for academic administration to develop students to have 21st century learning skills: a case study of Uttaradit Provincial Administrative Organization schools The population groups used in the Phase 1research were school administrators and teachers. Schools, Uttaradit Provincial Administrative Organization, a total of 47 students were obtained by selective selection. The target group in phase 2 is school administrators and teachers of Chiang Rai Provincial Administrative Organization schools. and Tonkaew Phadungpittayalai School Under the Chiang Mai Provincial Administrative Organization The number of administrators and teachers in each school is 6 peoples, totaling 12 people who are qualified. The tools used for data collection were questionnaires and group discussion forms. The statistics used in the data analysis were frequency, percentage, mean, standard deviation. and content analysis The results of the research revealed that the need for academic administration To develop students to have 21st century learning skills. The top 3 case studies of Uttaradit Provincial Administrative Organization schools are the development of innovative media and educational technology. development of learning resources and the development of learning processes There is a guideline for academic administration regarding media development, innovation and educational technology, namely the school has a teacher meeting to explain teachers before the semester starts about media, innovation, and educational technology to plan. Use the Microsoft award leading teachers to educate teachers so that all teachers can manage online teaching. Blended learning school and the school liaises with experts to provide advice and assistance to teachers in the use of media, innovation and educational technology to manage teaching and learning.